Genomic approaches for monitoring transmission dynamics of malaria: A case for malaria molecular surveillance in Sub–Saharan Africa - Mensah, Benedicta A.; Akyea-Bobi, Nukunu E.; Ghansah, Anita (Frontiers in Epidemiology, 2022)
Transmission dynamics is an important indicator for malaria control and elimination. Transmission indices with higher resolution (genomic approaches) will supplement our current measures of malaria transmission as we get closer to malaria elimination in sub-Saharan Africa (SSA) with a highly varied malaria environment. The current programmatic understanding of malaria transmission patterns is based primarily on epidemiologic/clinical data analyses, such as case counts, parasitological estimates of parasite prevalence and Entomological Inoculation Rates (EIR). To eliminate malaria from endemic settings however, we need ways of monitoring what is going on in the parasite population and how it will impact transmission. This is made possible through an evolving field of genomics/genetics and powerful tool development for studying parasite diversity, and complexity of infections among others in more depth and driven by the availability of parasite genome sequence data. Parasite genomic data from routinely collected blood samples for diagnosis and surveillance and potentially from other programmatic interventions provides a unique opportunity to track the spread of malaria parasites and shed additional light on intervention efficacy and should be encouraged to support country specific elimination activities, if malaria elimination is to see fruition globally. This review highlights several genetic approaches and their importance in better understanding transmission patterns in distinct topological settings across sub-Saharan Africa. The value of these methods, as well as the limitations of incorporating them into malaria surveillance to guide control and elimination strategies, are discussed.